2021
DOI: 10.3389/fimmu.2021.630892
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Resolved Atopic Dermatitis Shows Melanocyte and Immune Cell Activation Distinct From Healthy Control Skin

Abstract: Atopic dermatitis (AD) typically starts in infancy or early childhood, showing spontaneous remission in a subset of patients, while others develop lifelong disease. Despite an increased understanding of AD, factors guiding its natural course are only insufficiently elucidated. We thus performed suction blistering in skin of adult patients with stable, spontaneous remission from previous moderate-to-severe AD during childhood. Samples were compared to healthy controls without personal or familial history of ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 93 publications
1
22
0
1
Order By: Relevance
“…27 The liquid nature of the biopsy can enhance single-cell dissociation. 28 A major limitation of this method is the inability to capture deeper dermal regions, and therefore, dermal, endothelial cell and macrophage (Mφ) information cannot be provided. 27,28 Another parameter to be considered is the possibility of samples being frozen prior to processing, allowing sample processing at different time points.…”
Section: Technic Al Cons Ider Ationsmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The liquid nature of the biopsy can enhance single-cell dissociation. 28 A major limitation of this method is the inability to capture deeper dermal regions, and therefore, dermal, endothelial cell and macrophage (Mφ) information cannot be provided. 27,28 Another parameter to be considered is the possibility of samples being frozen prior to processing, allowing sample processing at different time points.…”
Section: Technic Al Cons Ider Ationsmentioning
confidence: 99%
“…28 A major limitation of this method is the inability to capture deeper dermal regions, and therefore, dermal, endothelial cell and macrophage (Mφ) information cannot be provided. 27,28 Another parameter to be considered is the possibility of samples being frozen prior to processing, allowing sample processing at different time points. However, reduction of cell numbers, and the alleviation of the cell transcriptome, are two major considerations.…”
Section: Technic Al Cons Ider Ationsmentioning
confidence: 99%
“…Recent development of single-cell RNA technology brought new insight of the characterization of T cells in AD skin ( 10 , 18 , 43 , 44 ). The lesional AD samples were characterized by expansion of T RM , Th2/Tc2, and Th22 cells.…”
Section: T Cells In Admentioning
confidence: 99%
“…Pathway enrichment analysis revealed enrichment of the immune response, antigen processing and presentation, and regulation of apoptosis in lesional AD T cells. In healed AD lesion of adults, it was suggested that a Th1-skewed immune profile is involved in the clinical remission ( 44 ). Interestingly, identification of specific populations of disease-linked immune cells maintaining an inflammatory phenotype in resolved AD, including Th2 and Tc2 cells, suggest that these cells can be crucial for disease recurrence ( 43 ).…”
Section: T Cells In Admentioning
confidence: 99%
“…Die Saugblasen‐Technik wurde mittlerweile in zwei weiteren Projekten derselben Gruppe angewandt: Bangert et al konnten zeigen, dass bestimmte T‐Zellen und Dendritische Zellen in behandelter Haut von Atopikern persistieren, die auch nach einjähriger, erfolgreicher Dupilumab‐Therapie mit kompletter klinischer Abheilung nicht zu eliminieren sind, und möglicherweise eine Art Krankheitsgedächtnis der Haut darstellen [5]. Rindler et al haben Saugblasen von Patienten mit spontan abgeheilter atopischer Dermatitis analysiert und Unterschiede im T‐Zell und Melanozyten‐Expressionsmuster im Vergleich zu gesunden Probanden festgestellt [6]. Somit stellt diese Technik eine vielversprechende Option für zukünftige translationelle Forschungsfragen in der Dermatologie dar.…”
Section: Abbildungunclassified